2021
DOI: 10.1002/hpja.524
|View full text |Cite
|
Sign up to set email alerts
|

Australian men's initial pathways into mental health services

Abstract: The comparatively low uptake of mental health services among Australian men has steadily improved following concerted public health efforts. 1 While this signals progress, poorly understood are why and how men engage in mental health care. Addressing this knowledge gap will help inform future mental health promotion efforts to meet men's needs and overcome engagement barriers. 2 A wealth of research has appraised facets of masculine socialisation that are thought to underpin men's mental ill health and apparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Apart from these attitudinal barriers, structural barriers such as lacking financial resources, not knowing what to look for in a therapist, or not knowing where to get help have further been identified as important factors that potentially hinder men from engaging in treatment (Lynch et al, 2018; Seidler et al, 2020). Lastly, Seidler et al (2022) recently reported that anxiety was the main reason for why men started psychotherapeutic treatment among a large sample of Australian men. However, the present study is not able to give a conclusive answer on this topic since these factors were not included in the surveys used for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these attitudinal barriers, structural barriers such as lacking financial resources, not knowing what to look for in a therapist, or not knowing where to get help have further been identified as important factors that potentially hinder men from engaging in treatment (Lynch et al, 2018; Seidler et al, 2020). Lastly, Seidler et al (2022) recently reported that anxiety was the main reason for why men started psychotherapeutic treatment among a large sample of Australian men. However, the present study is not able to give a conclusive answer on this topic since these factors were not included in the surveys used for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Far less attention has been paid to those men who do seek help, overcoming a plethora of both structural and attitudinal barriers in the process. Recent work in Australia has highlighted that up to 40% of help-seeking men are self-motivated in their initiation of contact with mental health services [ 10 ]. Yet additional Australian evidence reveals room for improvement in the extent to which practitioners are providing a service that meets men’s needs [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…These advertisements appeared for participants in the normal advertising panes on Facebook, and they were free to choose whether or not to click through the advertisement. Advertisements contained the following text, adapted from our previous male-specific help-seeking surveys [ 33 ]: “ Survey for men: Have you had any difficulties with your mental health during the COVID-19 pandemic? We want to hear about your experience.…”
Section: Methodsmentioning
confidence: 99%